Efektivitas Edukasi Berbasis Video dalam Meningkatkan Pengetahuan Remaja Tentang Balut Bidai - Rabiya Takumansang; Tezar Nusi; Sarwan Sarwan (Calory Journal Medical Laboratory Journal, 2025)
Musculosceletal trauma is one of the common injuries that occur among adolescents, particularly in the school environment. Knowledge about splint bandaging is crucial to prevent further complications. The use of video-based education media is considered effective in improving adolescents understanding of splint bandaging. This study aimed to assess the effectiviness of video-based education in increasing adolescents knowledge about splint bandaging. This research employed a pre-experimental design with a one-group pretest-posttest approach. The research sample consisted is students, totaling 34 respondents selected using accidental sampling. The research instrument was a knowledge questionnaire. Data were analyzed using the wilcoxon signed Rank Test Results showed that before intervention, most respondents had a low level of knowledge, with 26 respondents (76.5%) categorized as poor. After the intervension, a significant improvement was observed, with all respondents (100%) classified as having good knowledge . The Wilcoxon Signed Rank Test showed a P-Value = 0,000 < α 0,05. It can be concluded that video-based education is effective in improving adolescents knowledge regarding splint bandaging.